AICCRA: Strengthening Systems for Delivery of Climate Information Services (CIS) and Agro-Advisories to Farmers in Kenya - Chesoli, Rose (International Livestock Research Institute, 2024)
Climate change continues to pose significant challenges to Kenya’s agriculture sector, particularly for smallholder farmers. Kenya's climate is shaped by its diverse topography, spanning coastal lowlands to highland plateaus and mountains (Edame & Fonta, 2011). This geographical variation gives rise to a spectrum of climatic and ecological zones, encompassing hot and humid coastal regions, arid and semi-arid lands (ASALs) characterized by low rainfall and high temperatures, cool to temperate highlands with distinct wet and dry seasons, and variable climates in the Rift Valley (Government of Kenya, 2018). Overall, the country's water for domestic and agricultural use is derived from rivers and streams whose recharge depends on rainfall. However, climate change has led to shifts in rainfall seasonality, manifesting as delayed onsets and reduced durations of the rainy season impacting the availability of freshwater in Kenya (Government of Kenya, 2018).